Study of a fractional‐order model of chronic wasting disease. (21st January 2020) - Maji, Chandan; Mukherjee, Debasis; Kesh, Dipak
Abstract : This paper studies a fractional‐order modelling chronic wasting disease (CWD). The basic results on existence, uniqueness, non‐negativity, and boundedness of the solutions are investigated for the considered model. The criterion for local as well as global stability of the equilibrium points is derived. A numerical analysis for Hopf‐type bifurcation is presented. Finally, numerical simulations are provided to justify the results obtained.